What Is the Biological and Clinical Relevance of Fibrin? - Litvinov, Rustem I.; Weisel, John W. (Seminars in Thrombosis and Hemostasis, 2016)
As our knowledge of the structure and functions of fibrinogen and fibrin has increased tremendously, several key findings have given some people a superficial impression that the biological and clinical significance of these clotting proteins may be less than earlier thought. Most strikingly, studies of fibrinogen knockout mice demonstrated that many of these mice survive to weaning and beyond, suggesting that fibrin(ogen) may not be entirely necessary. Humans with afibrinogenemia also survive. Furthermore, in recent years, the major emphasis in the treatment of arterial thrombosis has been on inhibition of platelets, rather than fibrin. In contrast to the initially apparent conclusions from these results, it has become increasingly clear that fibrin is essential for hemostasis; is a key factor in thrombosis; and plays an important biological role in infection, inflammation, immunology, and wound healing. In addition, fibrinogen replacement therapy has become a preferred, major treatment for severe bleeding in trauma and surgery. Finally, fibrin is a unique biomaterial and is used as a sealant or glue, a matrix for cells, a scaffold for tissue engineering, and a carrier and/or a vector for targeted drug delivery.
Keywords: fibrin; fibrinogen; hemostasis; thrombosis; afibrinogenemia; hypofibrinogenemia; dysfibrinogenemia